PEMETAAN KUALITAS AIR SUNGAI DI SURABAYA - M. Khadik Asrori (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
Water is a vital resource for all living organisms. Water resources must be managed in a sustainable way to protect our environment and its beneficial uses for human life and other organisms. River water is one of the water resources for human life. One of the regions that use river water for water resources is Surabaya. Surabaya rivers are considered as the primary source of water used by the citizens. The water of the Surabaya River is the raw material of drinking water and one of the water supply source for PDAM Surabaya. Furthermore, the Surabaya River has been used not only as a water resource for people and industries but also as a place for industrial waste disposal. The increasing of industrial development has raised concerns about water consumption, so it is necessary to monitor the water quality of the Surabaya River to determine chemical, physical, and biological parameters.